Alfredo Dugès’ type specimens of amphibians and reptiles revisited - Flores-Villela, Oscar; Ríos-Muñoz, César A.; Magaña-Cota, Gloria E.; Quezadas-Tapia, Néstor L. (Zootaxa, 2016)
The type specimens of amphibians and reptiles of the Museo de Historia Natural Alfredo Dugès, at the University of Guanajuato (MADUG) were reviewed following Smith & Necker’s (1943) summary. Owing to this collection’s eventful history and its historical importance as the oldest herpetological collection in Mexico, a review of its conservation status was needed. After many years, the collection has received proper recognition at the University of Guanajuato with a portion of the herpetological types considered “Precious Assets” of the university. We found 34 type specimens pertaining to 18 taxa; six are additional specimens to those previously reported; six herpetological types are missing, including the body of the type of Adelophis copei. All specimens are in good to reasonable condition except for the type of Rhinocheilus antonii, which has dried out completely. All specimens are illustrated to show their condition.